Mapas do imaginário compartilhado na experiência do jogar: o videogame como agenciador de devaneios poéticos - Gasi, Flávia (2016)
Videogames, as the object of study in the field of communication, is a hybrid composed of computer technology, languages, logic, narrative and ludological systems, devices, avatars, players and gamer culture network. In this study, we understand that communication processes in videogames take place in the network, so that game spreads and active cyberspace, in a symbiosis machines, narratives and players, who share an imaginary constantly changing. Our hypothesis is that the shared imagery can be found and charted from the narratives of the experiences of the players. The Master's dissertation "The poetic imagery of the game: translations of imaginary and Greek myths in the creation of digital games process," had the goal was to understand the translations and passages of Greek myths in the videogame narratives. In this doctoral thesis, the proposal is to understand the imaginary built in game experience from mapping processes of poetic content emerging from the narratives of the players. To this end, we investigate the experience of playing, based on the idea of poetic reverie Bachelard in order to carry maps of the narratives, according to the imaginary mapping concept developed by Leão. The empirical object is in video games: Okami, Bioshock and Mass Effect 2. Our proposal is anchored on the idea of three types of poetry: intrinsic image, syncretism mythological and imaginary aura discussed in our dissertation. Our goal is to check the experience of players and how these poetics emerge in their narratives. The research method adopts the epistemological perspective of the communication processes and culture and involved: reading texts, conversations with players, analysis of conversations and mapping of shared imaginary. The dialogues with players were conducted in two stages: (1) as players experience their games, and (2) two years after the first meeting. The results of our research were: (1) to be affect is central for experiencing a central role in playing videogames; (2) the experience of having the central role on a game creates power struggles between what is possible in ludological narrative of the game and what the player wishes to be possible; (3) these conflicts are usually resolved in the experience of labyrinth, the unbinding of knots, and the desecration of power relations, which usually takes place via the creation of an emerging narrative by the player; (4) the experience of playing as central role experience can create poetical daydreams; (5) it is possible to map the imaginary experienced in the game experience through narratives through communication and the emergence of memory